Senyawa aktif monoterpenoid dan sesquiterpenoid dari minyak atsiri rimpang suku Zingiberaceae - Shifa, Hasna Nur; Marliani, Lia; Suhardiman, Aris (Universitas Islam Indonesia, 2023)
Background: Plants of the Zingiberaceae family are widely grown and cultivated in Indonesia. One of the uses of these plants by the community is as traditional medicine. The part of the plant that is often used as a traditional medicine in the Zingiberaceae family is the rhizome. The potential of Zingiberaceae as a drug is closely related to its pharmacological activity and the active compounds it contains. Essential oils are materials contained in the Zingiberaceae family and have the potential to be active compounds.Objective: This review article was compiled to study the compounds contained in the essential oil of the Zingiberaceae family and the biological activities of these compounds.Method: Article reviews were conducted using an electronic literature search method through journal portals such as Google Scholar, Science Direct, and Research Gate using keywords, namely identification of the chemical content of essential oils, rhizomes, Zingiberaceae, biological activity, and pharmacological activity.Results: This study found that the main terpenoid compounds in the essential oil from the rhizome of the Zingiberaceae family are α-cineol, β-pinene, β-sesquiphellandrene, and α-Zingiberene. Each of them has a different pharmacological activity, such as antibacterial, antiviral, or cytotoxic.Conclusion: The essential oil from the rhizomes of the Zingiberaceae family has great potential to be developed as a medicinal ingredient with antibacterial, antiviral, and anticancer properties. Before being used as a drug, it is necessary to carry out further research on toxicity, biopharmaceutical, and clinical research.Keywords: Essential oil, rhizome, Zingiberaceae, terpenoid Intisari Latar belakang: Tumbuhan suku Zingiberaceae banyak tumbuh dan dibudidayakan di Indonesia. Salah satu pemanfaatan tumbuhan tersebut oleh masyarakat adalah sebagai obat tradisional. Bagian tumbuhan yang sering dimanfaatkan sebagai obat tradisioal dari suku Zingiberaceae adalah rimpang. Potensi suku Zingiberaceae sebagai obat berhubungan erat dengan aktivitas farmakologi dan senyawa aktif yang dikandungnya. Minyak atsiri merupakan zat yang terkandung dalam suku Zingiberaceae dan berpotensi sebagai senyawa aktif. Tujuan: Review artikel ini disusun untuk mengkaji senyawa yang terkandung pada minyak atsiri rimpang tanaman suku Zingiberaceae dan aktivitas biologi dari senyawa tersebut. Metode: Review artikel dilakukan menggunakan metode pencarian literatur secara elektronik melalui portal jurnal seperti Google Scholar, Science Direct, dan Research Gate dengan menggunakan kata kunci yaitu identifikasi kandungan kimia minyak atsiri, rimpang, Zingiberaceae, aktivitas biologi, aktivitas farmakologi.Hasil: Senyawa terpenoid yang banyak terkandung dalam minyak atsiri rimpang suku Zingiberaceae, yaitu 1,8-cineol, α-pinene, β–pinene, β-sesquiphellandrene dan α-Zingiberene. Masing-masing memiliki aktivitas farmakologi berbeda seperti antibakteri, antivirus, dan sitotoksik.Kesimpulan: Minyak atsiri dari rimpang suku Zingiberaceae berpotensi besar untuk dikembangkan sebagai bahan obat seperti antibakteri, antivirus dan antikanker. Sebelum digunakan sebagai obat ,perlu dilakukan penelitian lebih lanjut mengenai toksisitas, biofarmasetika, dan penelitian secara klinis.Kata kunci: Minyak atsiri; rimpang; Zingiberaceae, terpenoid